2006
DOI: 10.1369/jhc.5a6805.2005
|View full text |Cite
|
Sign up to set email alerts
|

Intrastriatal Infusion of Liver Growth Factor Stimulates Dopamine Terminal Sprouting and Partially Restores Motor Function in 6-Hydroxydopamine-lesioned Rats

Abstract: Liver growth factor (LGF) is a mitogen for liver cells that shows biological activity in extrahepatic sites and may be useful for neuroregenerative therapies. The aim of this work was to investigate the effects of the intrastriatal (IS) infusion of LGF in the 6-hydroxydopamine rat model of Parkinson's disease. Tyrosine hydroxylase-positive innervation was significantly increased in the dopamine-denervated striatum of rats receiving intrastriatal LGF infusions (160 ng/day/rat × 15 days) as compared with a vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 55 publications
5
38
0
1
Order By: Relevance
“…In fact, they were completely restored to levels not different from those found in WKY normotensive rats. Second, the actions of LGF in vitro on VSMC were very rapid, in 48 h, a time course effect similar that found in liver (27) and in the striatum (52), suggesting that the first actions of LGF might be on cell/ECM balance, which in turn has a favorable impact on vascular and heart mechanics, reducing blood pressure. In the study of new antihypertensive treatments, to address the chicken and egg question, it has been common to include a group of animals treated with a general vasodilator, such as hydralazine or hydrochlorothiazide, or a combination of both.…”
Section: Limitations Of the Studysupporting
confidence: 57%
See 4 more Smart Citations
“…In fact, they were completely restored to levels not different from those found in WKY normotensive rats. Second, the actions of LGF in vitro on VSMC were very rapid, in 48 h, a time course effect similar that found in liver (27) and in the striatum (52), suggesting that the first actions of LGF might be on cell/ECM balance, which in turn has a favorable impact on vascular and heart mechanics, reducing blood pressure. In the study of new antihypertensive treatments, to address the chicken and egg question, it has been common to include a group of animals treated with a general vasodilator, such as hydralazine or hydrochlorothiazide, or a combination of both.…”
Section: Limitations Of the Studysupporting
confidence: 57%
“…We have previously demonstrated that the excessive ECM deposition by VSMC from SHR is related to a cellular defect in SHR, consisting of defective proliferation, but enhanced cell survival of hypertrophied diploid cells, which keep producing ECM, without normal turnover (7). On the other hand, the regenerative actions of LGF in several biological systems have been linked to its mitogenic effects (26,27,35,52). In our previous study, we also reported that LGF was able to improve the reduced VSMC density and abnormally high ploidy in carotid arteries from SHR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations